1973
DOI: 10.1042/bj1360611
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of ribonucleic acid polymerase activity in vitro by prostatic steroid–protein receptor complexes

Abstract: A system has been developed which allows the stimulation in vitro of prostatic RNA polymerase by prostatic 5alpha-dihydrotestosterone-protein receptor complexes prepared from the tissues of castrated rats. The reconstitution in vitro of such a system necessitates the purification of several subcellular components. Two 5alpha-dihydrotestosterone-receptor complexes are located in the prostatic soluble supernatant fraction, separable by selective ammonium sulphate fractionation, and one complex can be isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Although proof of the participation of androgen receptors in the direct control of cell proliferation, 5a-reductase activity and secretory acid phosphatase activity is contingent on a fuller understanding of the interaction of androgen receptors with chromatin acceptor sites (Davies & Griffiths, 1973;Mainwaring et al, 1976;Rennie, 1979), the results obtained in the present investigation favour the hypothesis that androgen receptors, rather than non-receptor-bound nuclear androgen, modulate cell proliferation and 5a-reductase activity. Since the association constant (Ka) for the binding of dihydrotestosterone to chromatin-bound receptor sites is of the order of 5 x 107M-1 (Rennie, 1979), and since the nuclear concentration of receptor sites is far lower than the concentration of dihydrotestosterone, the most obvious function of the excess nuclear dihydrotestosterone is to ensure that all the receptor sites within the nucleus are occupied with androgen.…”
Section: Effects Of Dose On the Intracellular Concentration Of Dihydrsupporting
confidence: 70%
See 1 more Smart Citation
“…Although proof of the participation of androgen receptors in the direct control of cell proliferation, 5a-reductase activity and secretory acid phosphatase activity is contingent on a fuller understanding of the interaction of androgen receptors with chromatin acceptor sites (Davies & Griffiths, 1973;Mainwaring et al, 1976;Rennie, 1979), the results obtained in the present investigation favour the hypothesis that androgen receptors, rather than non-receptor-bound nuclear androgen, modulate cell proliferation and 5a-reductase activity. Since the association constant (Ka) for the binding of dihydrotestosterone to chromatin-bound receptor sites is of the order of 5 x 107M-1 (Rennie, 1979), and since the nuclear concentration of receptor sites is far lower than the concentration of dihydrotestosterone, the most obvious function of the excess nuclear dihydrotestosterone is to ensure that all the receptor sites within the nucleus are occupied with androgen.…”
Section: Effects Of Dose On the Intracellular Concentration Of Dihydrsupporting
confidence: 70%
“…Results from experiments performed in vitro by several groups (Davies & Griffiths, 1973;Mainwaring & Jones, 1975;Hu et al, 1975) have indicated that androgen-receptor complexes directly modulate the transcription of chromatin by RNA polymerase. Androgen receptors have also been implicated in the regulation of DNA synthesis and cell proliferation in the regenerating prostate (Coffey, 1974;Rennie et al, 1975;Van Doorn et al, 1976).…”
mentioning
confidence: 99%
“…Such a series of initial experiments is summarized in Fig. 1 (Mainwaring & Peterken, 1971;Davies & Griffiths, 1974). Degraded receptor, after treatment with N-ethylmaleimide (Mainwaring, 1969b), is totally inactive.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…To examine differences in physiological properties of receptor complexes which showed different characteristics of the nuclear binding, stimulation of RNA-polymerase in the rat ventral prostate by the DHT-prostate receptor complex was studied. However, Fig.3 this attempt was not successful, since, in our hand, no significant stimulation of RNApolymerase in the rat ventral prostate was obtained even with the DHT-prostate receptor complex which was not pretreated with heterogenous nuclei under the similar incubation conditions described by Davies and Griffiths (1973) (data not shown). Comparison of other properties of the receptor complex "absorbed" by heterogenous nuclei with those of the "unabsorbed" one in liver and prostate is under examination in this laboratory.…”
Section: Endocrinolmentioning
confidence: 87%